PREPARING FUTURE TEACHERS FOR EDUCATIONAL ACTIVITY BASED ON INNOVATIVE TECHNOLOGIES - F. O. Mirzayeva; Abulova M. K. (Galaxy International Interdisciplinary Research Journal, 2023)
This article reflects on the effective methods of formation of creativity and technology application skills of future specialists in higher education in an innovative educational environment, as well as improving the effectiveness of education, placing the person at the center of education and independent youth. special attention is paid to the issue of ensuring their education.